Precision Healthcare: Leveraging Value Chain Analysis of Strategic Information Systems and Information Technology to Enhance Hospital Outcomes - Kamarudin, Kamarudin (Jurnal Riset Sistem dan Teknologi Informasi, 2025)
In the healthcare digitalization era, leveraging strategic information systems (IS) and information technology (IT) through value chain analysis has emerged as a pivotal approach to enhance hospital outcomes. This study aims to develop a framework for integrating IS/IT strategies at Datu Sanggul Hospital, a Class C facility in South Kalimantan, to achieve precision healthcare delivery. The research methodology encompasses data collection via document studies, stakeholder interviews, and observations, coupled with rigorous data analysis and validation techniques. A strategic model formulates algorithms and system architectures guiding implementation of critical IS/IT initiatives like telemedicine, customer relationship management, and executive information systems. Robust IT strategies, including data center development, cloud computing, and disaster recovery planning, optimize operations and resource management. Mapping business needs to tailored IS solutions ensures precision across financial reporting, inventory management, employee training, and interdepartmental collaboration. The proposed approach aligns IS/IT strategies with operational objectives through value chain analysis, enhancing patient care quality, operational efficiency, and resource optimization. Positioning the institution for precision medicine, this framework drives innovation and improves health outcomes in healthcare's evolving landscape.